Location, Pricing, and Facilities as Determinants of Sports Field Rental Business Success in Palopo City - Muh. Ramli; Nengsi Sudirman; Afrianto; Waldi (Journal JEKAMI, 2026)
This study investigates the influence of location, pricing, and facilities on the success of sports field rental businesses in Palopo City, Indonesia. As competition in the sports service industry intensifies, identifying the determinants of business success has become increasingly important for improving competitiveness and long-term sustainability. A quantitative research design with a survey approach was employed. Data were collected from 96 customers of Sinar Setuju Sports Field using purposive sampling and structured questionnaires. The measurement instrument was assessed through validity and reliability testing, while the proposed hypotheses were examined using multiple linear regression analysis. The findings reveal that location, pricing, and facilities each have a positive and statistically significant effect on business success. Among these variables, facilities demonstrate the strongest influence, followed by pricing and location, indicating that well-maintained and comprehensive facilities play a critical role in enhancing customer satisfaction and supporting business performance. Strategic accessibility and competitive pricing also contribute significantly to attracting and retaining customers. These findings suggest that service providers should prioritize investments in facility quality while maintaining accessible locations and market-oriented pricing strategies to strengthen competitive advantage. This study contributes to the service marketing and small business management literature by providing empirical evidence on the key drivers of sports field rental business success in an emerging regional market. The results also offer practical insights for entrepreneurs and business managers seeking to improve operational performance and achieve sustainable business growth within the expanding sports service industry.